(International) R&D collaboration and SMEs: The effectiveness of targeted public R&D support schemes - Hanna Hottenrott; Cindy Lopes-Bento (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This study analyses the impact and effectiveness of targeted public support for R&D investment at the firm level. We test whether the policy design aiming at incentivizing (international) collaboration and R&D in SMEs achieves input as well as output additionality. Our results show that the targeted public subsidies trigger R&D spending, especially so in internationally collaborating SMEs. We further evaluate the different impact of privately financed and publicly-induced R&D investment on innovation performance. The results confirm that the publicly-induced R&D is productive as it translates into marketable product innovations. While both types of R&D investments trigger significant output effects, the effect of policyinduced R&D investment on sales from market novelties is highest for international collaborators as well as for SMEs.
Keywords: C14; C30; H23; O31; O38; 330; Public Innovation Policy; Subsidies; R&D; SMEs; International Collaboration; Treatment Effects